2008
DOI: 10.1186/1477-044x-6-2
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermic treatment of DMBA-induced rat mammary cancer using magnetic nanoparticles

Abstract: Background: We have developed magnetite cationic liposomes (MCLs) and applied them as a mediator of local hyperthermia. MCLs can generate heat under an alternating magnetic field (AMF). In this study, the in vivo effect of hyperthermia mediated by MCLs was examined using 7,12-dimethylbenz(a)anthracene (DMBA)-induced rat mammary cancer as a spontaneous cancer model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…17,[38][39][40] Direct intratumoral injections of MNPs followed by induction heating has shown some benefit in controlling tumor growth. 38,[41][42][43][44][45][46][47][48][49] Direct intratumoral injection was used in the first MNP hyperthermia clinical trial treating a prostate cancer using a 100 kHz machine designed for human patients, 50 and later in human glioma trials 51,52 which demonstrated safety and some benefit. Heating was obtained, but due to inhomogeneous MNP distribution, complete tumor eradication was not possible.…”
Section: Introductionmentioning
confidence: 99%
“…17,[38][39][40] Direct intratumoral injections of MNPs followed by induction heating has shown some benefit in controlling tumor growth. 38,[41][42][43][44][45][46][47][48][49] Direct intratumoral injection was used in the first MNP hyperthermia clinical trial treating a prostate cancer using a 100 kHz machine designed for human patients, 50 and later in human glioma trials 51,52 which demonstrated safety and some benefit. Heating was obtained, but due to inhomogeneous MNP distribution, complete tumor eradication was not possible.…”
Section: Introductionmentioning
confidence: 99%
“…To date, for example, it is still unclear how successful are the DMBA tumor induction protocols used in research in generating tumors. In a study on hyperthermic treatment of DMBA-induced rat mammary cancer using magnetic nanoparticles, Motoyama et al (46) report, for example, that of 20 rats used only 4 exhibited "multiple growths of tumors at 1-3 sites in the body". This is not surprising given that as early as 1969 (47), it was pointed out that the assumption that the growth of neoplasms is independent of the initiating stimulus, once such neoplasms become fully established, is not universally valid for the induction of a wide variety of hepatomas by different doses and schedules of hepatocarcinogens (48) as well as for the induction of mammary tumors induced in rats exposed to different schedules of DMBA.…”
Section: Discussionmentioning
confidence: 99%
“…The rats were exposed to 3 series of hyperthermia treatments for 30 min each. The treated tumours were well controlled over a 30-day observation period showing an induction of immunological antitumour activity mediated by the MCLs (Motoyama et al, 2008). The use of anti-HER2 immunoliposomes containing nanomagnetic particles (HMLs) for anti-HER2 antibody therapy and tumour-specific hyperthermia has been exploited for many researche groups.…”
Section: Magnetic Nanoparticle Induced Hyperthermiamentioning
confidence: 99%